2012
DOI: 10.1016/j.mcp.2012.01.001
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of SCCmec-associated phenol-soluble modulin in staphylococci

Abstract: Please cite this article as: Monecke S, Engelmann I, Archambault M, Coleman DC, Coombs GW, Cortez de Jäckel S, Pelletier-Jacques G, Schwarz S, Shore AC, Slickers P, Ehricht R, Distribution of SCCmecassociated phenol-soluble modulin in staphylococci, Molecular and Cellular Probes (2012), doi: 10.1016/ j.mcp.2012 This is a PDF file of an unedited manuscript that has been accepted for publication. As a service to our customers we are providing this early version of the manuscript. The manuscript will undergo cop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 26 publications
1
22
0
Order By: Relevance
“…This is the first report to reveal that the regulatory role of a mobile genetic element-encoded factor on host bacterial virulence is conserved among the species incorporating the mobile genetic element. Because the SCC mec carrying psm-mec is widely observed among staphylococcal species, including S. aureus, S. epidermidis, S. haemolyticus, S. hominis, S. pseudintermedius, S. saprophyticus, S. fleurettii, S. vitulinus, and S. simulans [14], [17], the inhibitory effect of psm-mec against exotoxin production is assumed to confer conserved advantages to staphylococcal bacteria in their survival in host animals and may cause a positive effect on the dissemination and maintenance of SCC mec .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This is the first report to reveal that the regulatory role of a mobile genetic element-encoded factor on host bacterial virulence is conserved among the species incorporating the mobile genetic element. Because the SCC mec carrying psm-mec is widely observed among staphylococcal species, including S. aureus, S. epidermidis, S. haemolyticus, S. hominis, S. pseudintermedius, S. saprophyticus, S. fleurettii, S. vitulinus, and S. simulans [14], [17], the inhibitory effect of psm-mec against exotoxin production is assumed to confer conserved advantages to staphylococcal bacteria in their survival in host animals and may cause a positive effect on the dissemination and maintenance of SCC mec .…”
Section: Resultsmentioning
confidence: 99%
“…The function of psm-mec to inhibit exotoxin production and to increase biofilm formation might contribute to alleviate excess damage to host animals and to survive in the host environment. The psm-mec exists not only in S. aureus , but also in other staphylococcal species [17]. It has remained unclear, however, whether the regulatory function of psm-mec is conserved among the staphylococcus species carrying SCC mec, which needs the conserved interaction between the mobile genetic element-encoded psm-mec and core genome encoded-virulence factors.…”
Section: Introductionmentioning
confidence: 99%
“…The psm-mec locus is found in the J2 region adjacent to mecI of the class A mec gene complex in several widespread HA-MRSA lineages, but most prominently in Sequence Type (ST) 5, ST36, ST45, ST225, and ST239 strains (Deurenberg and Stobberingh, 2009; Nübel et al, 2010; Castillo-Ramirez et al, 2012; Schulte et al, 2013), which all have either SCC mec types II or III (Chatterjee et al, 2011; Monecke et al, 2012; Josten et al, 2014). However, more detailed analysis revealed that the psm-mec locus is found in SCC mec types II, IIA, IIB, IID, III, and VIII of many Staphylococcus species (Monecke et al, 2012; Shore and Coleman, 2013).…”
Section: The Distribution Of the Psm-mec Locus In Sccmecmentioning
confidence: 99%
“…However, more detailed analysis revealed that the psm-mec locus is found in SCC mec types II, IIA, IIB, IID, III, and VIII of many Staphylococcus species (Monecke et al, 2012; Shore and Coleman, 2013). …”
Section: The Distribution Of the Psm-mec Locus In Sccmecmentioning
confidence: 99%
“…Acquisition of SCCmec not only gives S. aureus the ability to become resistant to almost the entire class of ␤-lactam antibiotics but also modulates the virulence (35) and agr quorum sensing (36) in some strains. SCCmec types II, III, and VIII and some irregular or truncated SCCmec elements harbor the toxin gene psm-mec (37), which codes for a regulatory RNA and modulates the virulence of MRSA through suppressing AgrA translation (38). As displayed before, SCCmec can be excised from or integrated into bacterial chromosomes mediated by CcrAB recombinases, which are encoded by ccrAB genes (5).…”
Section: Discussionmentioning
confidence: 99%